النظرية الأخلاقية في القرآن الكريم ـ كتاب دستور الأخلاق في القرآن الكريم لمحمد عبد الله دراز أنموذجا ـ - الأعور, نسيمة; دردوري, رقية (University of eloued جامعة الوادي, 2021)
حاولنا من خلال هذه الدراسة تبيين أسس النظرية الأخلاقية في القرآن الكريم، وذلك بالاعتماد على كتاب دستور الأخلاق في القرآن الكريم لمحمد عبد الله دراز، وكذا توضيح كفية استخدام الأخلاق الإسلامية في معالجة مشاكل العصر، وكذا كيفية استخراجها من القصص الواردة في القرآن الكريم. وقد جاء اشتغالنا على هذا الموضوع بتوظيف منهج استقرائي في إطار التأصيل والاستدلال على النظرية الأخلاقية في القرآن الكريم، وكذا المنهج الوصفي التحليلي إضافة إلى المنهج المقارن. وتهدف هذه الدراسة إلى إظهار مكانة الأخلاق في القرآن الكريم ومدى حاجة البشرية لها. ومن أهم نتائج هذه الدراسة أن النظرية الأخلاقية في القرآن الكريم عند محمد عبد الله دراز تقوم على خمسة أسس وهي أساس الإلزام وأساس المسؤولية وأساس الجزاء وأساس النية والدوافع وكذا أساس الجهد، وأن الأستاذ طه عبد الرحمان قدم إضافة معتبرة في هذا الباب حيث استخرج النظرية الأخلاقية في القرآن الكريم من خلال أبرز القصص الموجودة فيه. كما شرح دور هذه الأخلاق في حل مشكلات العصر وضمان حقوق البشر فيما بينهم. Through this study, we tried to clarify the foundations of the moral theory in the Holy Qur’an, by relying on the book “The Code of Ethics in the Holy Qur’an” by Mohammed Abdullah Daraz, as well as clarifying how to use Islamic ethics in addressing the problems of the time, as well as how to extract it from the stories contained in the Holy Qur’an. Our work on this subject came by employing an inductive approach within the framework of rooting and inference on the moral theory in the Holy Qur’an, as well as the descriptive analytical approach in addition to the comparative approach. This study aims to show the status of ethics in the Noble Qur’an and the extent to which humanity needs it. The most important results of this study is that the moral theory in the Noble Qur’an according to MOhammed Abdullah Daraz is based on five foundations, which are the basis of obligation, the basis of responsibility, the basis of punishment, the basis of intention and motives, as well as the basis of effort. The Holy Quran through the most prominent stories in it. He also explained the role of this morality in solving the problems of the time and ensuring the rights of human beings among them
عقيدة
Keywords: "النظرية الأخلاقية .القرآن الكريم محمد عبد الله دراز . آفاق."; Ethical theory .the Holy Quran- Muhammad Abdullah Draz -